👤

1)Aratati ca : 1) (x+Y+z)([tex] \frac{1}{x}+ \frac{1}{y} + \frac{1}{z} [/tex] ) ≥ 9 2,)Aratati ca pt orice numere reale x,y,z ,diferite doua cate doua,sunt adv egalitatile : a) [tex] \frac{1}{(x-y)(x-z)}+ \frac{1}{(y-x)(y-z)} + \frac{1}{(z-x)(z-y)} [/tex] = 0 b)[tex] \frac{x}{(x-y)(x-z)} + \frac{y}{(y-x)(y-z)} + \frac{z}{(z-x)(z-y)} [/tex] =0 3)Verificati ID lui Lagrange: ([tex]( a^{2} + b^{2} + c^{2} )( x^{2} + y^{2} + z^{2} ) [/tex] = (ax+by+cz)patrat + (ay-bx)patrat + (cx-az)patrat + (bz-cy) patrat

Răspuns :

1.stim   ( x + y +z ) /3 ≥∛x∛y∛z
si  [ 1 /x +1 /y + 1/z]  / 3 ≥ ∛1/x ·∛1 /y ·∛1 /z 
⇒ (  x +y +z )  · [1 /x + 1 /y +1 /z ] ≥ 3 ·3
 a.   1 / ( x -y) · ( x -z )  -  1 / ( x - y)·( y -z)  + 1  / ( x -z)· ( y -z) = 
                          ( z -x)·( z -y) = -1 ·( x -z) · ( -1) ·( y -z) 
= [ y -z  - ( x -z)   + x -y ] / ( ( x - y)·( x -z)· ( y -z) = 
   = [ y -z  - x + z + x - y ] / ( x -y)· ( x -z) · ( y -z)  = 0
b.  [ x / ( x -y )· ( x -z)   - y / ( x -y)· ( y -z)  +z / ( x -z)·( y -z)] =
     = [ xy  - xz -  xy  + yz + xz  - yz ] / ( x - y)· ( y -z)· ( x - z) = 
                 = 0